A contamination-free lateral flow platform for point-of-care virus detection in wastewater - Zhejia Sun; Fan Wang; Keyue Zhang; Huawei Yang; Baodong Song; Changhua He; Yingzi Lin; Yihan Yang; Xiaohong Zhou (Environmental Chemistry Letters, 2026)

Beyond conventional biochar: Sulfur-iron modification unlocks redox control for synergistic cadmium-arsenic sequestration in paddy soils - Zihao Liang; Hua Lin; Honghu Zeng; Sze-Mun Lam; Jin-Chung Sin; Xuehong Zhang; Guo Yu; Mi Feng; Yanpeng Liang; Huawei Li; Yuxi Lu; Gongning Chen (Environmental Research, 2026)

Predicting heavy metal impacts on soil ammonia oxidation during sludge land application: An interpretable framework integrating mechanistic models and machine learning - Jianju Li; Xinran Du; Zhiyuan Pan; Lin Si; Huawei Wang; Weihua Li; Rongxing Bian; Yingjie Sun; Liangliang Wei (Journal of Environmental Management, 2026)

Research progress on NSP4 protein of porcine reproductive and respiratory syndrome virus - Xiaolin Lan; Fang Liang; Gan Li; Yaqiong Ye; Feng Li; Chen Lv; Kexin Liu; Zhiyu Yang; Ruyu Sun; Keshan Zhang; Lin Wang; Huawei Li; et al. (Veterinary Research Communications, 2026)

Human settlement doubled global oceanic island erosion and fire regimes during the early colonization stage - Fan Zhang; Huawei Wang; Chuan-Chou Shen; Jian Lin; Kai Zhou; Yongshun Chen; Kunshan Bao; Xinxin Li (Global and Planetary Change, 2026)

Multifaceted Role of RIMBP2 in Promoting Hearing in Murine Cochlear Hair Cells - Menghui Liao; Xin Chen; Ling Lu; Qing Liu; Rongrong Guo; Yuyang Qiu; Yangnan Hu; Yuhua Zhang; Qiaojun Fang; Panpan Zhang; Yige Li; Shuijin He; et al. (Neuroscience Bulletin, 2026)

Stream position matters in a least-disturbed catchment? Multifaceted biodiversity indices and community assembly of macroinvertebrates along watercourse - Huawei Bao; Zongwei Lin; Guohao Liu; Yixia Wang; Yaochun Wang; Jiuli Shi; Lishani Wijewardene; Naicheng Wu (Journal for Nature Conservation, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Genome-Wide Identification and Expression Analysis of Genes Related to Cannabinoid Biosynthesis Pathways in Seed Hemp - Zuqing Yang; Huawei Wei; Xueqing Pan; Jiahui Chen; Huifan Kang; Yuxin Lin; Shaoqiang Jiang; Xuping Feng; Aifen Tao; Jianmin Qi; Jiantang Xu; Hongmei Kang; et al. (Tropical Plant Biology, 2025)

Actin–myosin complex dissociation initiates programmed cell death during cold storage of grass carp muscle - Xin Xiong; Huijuan Zhang; Lin Chen; Peipei Dou; Tianzhuo Huang; Shuai Zhuang; Yuqing Tan; Huawei Ma; Hui Hong; Yongkang Luo (Food Research International, 2025)

A novel dual-channel fluorescent probe for the detection of peroxynitrite anions and lipid droplets in epileptic disease - Yingxin Guo; Huawei Huang; Qian Zhang; Hongjian Wang; Miaomiao Liu; Weiying Lin (Analytica Chimica Acta, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Impact of Carbon and Nitrogen Assimilation in Sargassum fusiforme (Harvey) Setchell due to Marine Heatwave Under Global Warming - Xingda Sheng; Xiaojie Zuo; Lin Luo; Guanfeng Pang; Huawei Zhang; Kit Wayne Chew; Dongshun Fang; Binbin Chen; Mingjiang Wu (Global Change Biology, 2025)
Because of the rising global temperatures, Sargassum fusiforme (Harvey) Setchell, a commercially valuable seaweed, has experienced reduced yield and quality due to high temperatures from marine heatwave events. However, the mechanisms underlying the effects of heatwave stress on S. fusiforme remain unclear. In this study, the mechanisms of heatwave stress on the carbon and nitrogen assimilation processes in S. fusiforme were analyzed. These results indicated that heatwave stress, especially at 30°C for 12 days, significantly increased the levels of hydrogen peroxide (83%), malondialdehyde (84.7%), and relative conductivity (16.5%) in algae, which suggested an increase in algal damage. Morphologically, heatwave stress damaged the thylakoid structure and reduced the photosynthetic efficiency of algae and accumulated NADPH, ATP, and α‐ketoglutarate significantly, resulting in decreased content of mannitol, the photosynthetic product. Additionally, physiological and transcriptomic results revealed that heatwave stress inhibited the rate of nitrate absorption rate and the activities of the most enzymes associated with nitrogen accumulation, while significantly upregulating glutamate dehydrogenase (GDH), suggesting a crucial role for GDH in S. fusiforme 's adaptation to heatwave stress. In terms of amino acid composition, proline and alanine were the most sensitive to heatwave treatment. Moreover, under the natural heatwave environment simulation validation experiment, the algae showed the same physiological performance as under laboratory conditions. The results indicated that marine heatwave events increased oxidative damage in S. fusiforme and inhibited carbon and nitrogen absorption and assimilation, ultimately leading to negative effects on the growth of algae. Thus, in the context of rapid global warming exacerbating marine heatwave events, our study provides valuable insights for high‐temperature‐resistant breeding and ecological management in coastal aquaculture.

Evaluation of pollution potential in swine manure across growth stages: Impact of dietary nutrients and management strategies - Hongyong Fan; Chenghao Li; Wenxuan Zhang; Chaoxiang Liu; Olusegun K. Abass; Lin Liu; Xu Huang; Yingjie Sun; Huawei Wang; Maureen W. Gesiye; Wushan Chen (Science of The Total Environment, 2025)

Waste classification strategy based on multi-scale feature fusion for intelligent waste recycling in office buildings - Zongjing Lin; Huxiu Xu; Maoying Zhou; Ban Wang; Huawei Qin (Waste Management, 2024)

Caspase-3 interactions with calpain and cathepsin L: Implications for protein stability and quality in fish fillets during postmortem storage - Xiong Xin; Ding Ning; Zhuang Shuai; Dou Peipei; Feng Ruifang; Tan Yuqing; Ma Huawei; Chen Lin; Hong Hui; Luo Yongkang (Food Bioscience, 2024)

Distribution characteristics, sources and risk assessment of heavy metals in the surface sediments from the largest tributary of the Lancang River in the Tibet Plateau, China - Min Liu; Liangyuan Zhao; Li Lin; Yuting Zhang; Huawei Huang; Wei Deng; Yunjiao He; Jingxiang Tao; Yuan Hu; Luyi Nan; Yu Xuan Zhu (Environmental Geochemistry and Health, 2024)

Development of 3D-iNET ORION: a novel, pre-clinical, three-dimensional in vitro cell model for modeling human metastatic neuroendocrine tumor of the pancreas - Jan Strnadel; Mark A. Valasek; Grace Y. Lin; Huahui Lin; Ann M. Ponsford Tipps; Sang Myung Woo; Ken Fujimura; Huawei Wang; Sunkyu Choi; Jack Bui; Christopher Hermosillo; Kristen Jepsen; et al. (Human Cell, 2024)
Neuroendocrine tumors (NETs) of the pancreas are rare neoplasms that present complex challenges to diagnosis and treatment due to their indolent course. The incidence of pancreatic neuroendocrine tumors has increased significantly over the past two decades. A limited number of pancreatic neuroendocrine cell lines are currently available for the research. Here, we present 3D-iNET ORION, a novel 3-dimensional (spheroid) cell line, isolated from human pancreatic neuroendocrine tumor liver metastasis. Three-dimensionally grown (3D) cancer cell lines have gained interest over the past years as 3D cancer cell lines better recapitulate the in vivo structure of tumors, and are more suitable for in vitro and in vivo experiments. 3D-iNET ORION cancer cell line showed high potential to form tumorspheres when embedded in Matrigel matrix and expresses synaptophysin and EpCAM. Electron microscopy analysis of cancer cell line proved the presence of dense neurosecretory granules. When xenografted into athymic mice, 3D-iNET ORION cells produce slow-growing tumors, positive for chromogranin and synaptophysin. Human Core Exome Panel Analysis has shown that 3DiNET ORION cell line retains the genetic aberration profile detected in the original tumor. In conclusion, our newly developed neuroendocrine cancer cell line can be considered as a new research tool for in vitro and in vivo experiments.

A fluorescence probe for imaging lipid droplet and visualization of diabetes-related polarity variations - Zehua Chen; Lizhou Yue; Yingxin Guo; Huawei Huang; Weiying Lin (Analytica Chimica Acta, 2024)

N2O emission in temperate seagrass meadows: Fluxes, pathway and molecular mechanism - Qianling He; Huawei Qin; Lin Yang; Wenwen Tan; Daode Ji; Jianbai Zhang; Xiaoli Zhang (Marine Environmental Research, 2024)

Particulate polycyclic aromatic hydrocarbons and metals, DNA methylation and DNA methyltransferase among middle-school students in China - Wen Gu; Ting Wang; Yang Lin; Yanhua Wang; Yuanyuan Chen; Yufei Dai; Huawei Duan (Science of The Total Environment, 2024)

Synergistic removal performance and mechanism of Cd(II) and As(III) from irrigation water by iron sulfide-based porous biochar - Yuxi Lu; Honghu Zeng; Hua Lin; Yanpeng Liang; Mi Feng; Zijian Zhou; Zihao Liang; Huawei Li; Gongning Chen (Environmental Science and Pollution Research, 2024)

Simultaneous mitigating the bioavailability of cadmium and arsenic in paddy soil by two carbon-iron composites: A field-scale evaluation - Gongning Chen; Yuxi Lu; Mi Feng; Hua Lin; Yanpeng Liang; Zijian Zhou; Zihao Liang; Huawei Li; Honghu Zeng (Bioresource Technology Reports, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Inhalable mixture of polycyclic aromatic hydrocarbons and metals, DNA oxidative stress and nasal ribosomal DNA copy number amplification: Direct and indirect effect analyses among population - Yanhua Wang; Tao Meng; Liya Zhang; Yang Lin; Nan Wu; Huige Yuan; Zhizhou He; Yong Niu; Yufei Dai; Xing Zhao; Huawei Duan (Journal of Hazardous Materials, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Study on extract-pyrolysis cascading utilization characteristics of typical biomass using imidazolium-based ionic liquids - Tiantian Jiao; Shaojie Lin; Guangming Bai; Chuhan Ren; Yaqing Zhang; Xiangping Li; Huawei Zhang; Peng Liang (Fuel, 2023)

Inactivation of Microcystis aeruginosa by H2O2 generated from a carbon black polytetrafluoroethylene gas diffusion electrode in electrolysis by low-amperage electric current - Yuting Zhang; Li Lin; Di Jia; Lei Dong; Xiong Pan; Min Liu; Huawei Huang; Yuan Hu; John C. Crittenden (Environmental Pollution, 2023)

Screening and characterization of sex-specific markers by NGS sequencing in Spinibarbus hollandi with implication of XY sex determination system - Chong Han; Wenwei Huang; Suhan Peng; Jiangwei Zhou; Huawei Zhan; Lin Gui; Wenjun Li; Qiang Li (Aquaculture, 2023)

Microplastic contamination in coral reef fishes and its potential risks in the remote Xisha areas of the South China Sea - Lei Huang; Qian P. Li; Hengxiang Li; Lang Lin; Xiangrong Xu; Xiaojie Yuan; Jayamini B. Koongolla; Huawei Li (Marine Pollution Bulletin, 2023)

A “hydroxyl radicals standard” for evaluating the efficacy of anti-asthma drugs by using a two-photon NIR optical sensor - Lizhou Yue; Guofang Li; Zehua Chen; Lixuan Dai; Huawei Huang; Hao Li; Weiying Lin (Chemical Engineering Journal, 2023)

Marine eco-civilization performance evaluation in Oujiang Estuary, Zhejiang Province, China - Ying Lin; Huawei Zhang; Guanqiong Ye; Jingang Jiang; Qutu Jiang (Environment, Development and Sustainability, 2023)

The scaling of leaf nitrogen and phosphorus along a phosphorus availability gradient in a subtropical forest - Jiahao Wen; Janice Brahney; Yaoben Lin; Zhiliang Ma; Ningxiao Sun; Ji Zheng; Huawei Ji; Hongzhang Kang; Baoming Du; Guopeng Liang; Muhammad Umair; Chunjiang Liu (Plant Ecology, 2022)

Equivalent Aerodynamic Design of Blade for Offshore Floating Wind Turbine Model - Jiahuan Lin; Huawei Duan; Baoming Xu; Yangwei Wang; Jun Zhang (Journal of Marine Science and Engineering, 2022)
The Froude-scaled offshore floating wind turbine model is inevitably affected by the Reynolds number effect, making the model unable to correctly reproduce the thrust performance of the reference wind turbine (RWT). To solve this problem, an Xfoil-AirfoilPrep-Matlab (XAM) system and a wide tip speed ratio search method (WTSM) are proposed to design a wide tip speed ratio (TSR) thrust-match model blade. The XAM system is utilized to select the best airfoil for WTSM by calculating the lift and drag coefficients of several airfoils. The WTSM is utilized to optimize the blade chord and twist. It formalizes the blade chord and twist by polynomials and then optimizes the polynomial coefficients. The thrust coefficients construct the optimization object at different TSRs. For validating the effect of the redesigned blade, the thrust performance is compared to that of the RWT blade. In addition, the thrust performance of redesigned blade at different pitch angles is also calculated and compared to those of the RWT blade. Results show that the thrust performance of redesigned blade matches well with that of the RWT blade at 0 pitch angle, and it can also match the variations of that of the RWT blade at the other pitch angles well.

Investigation on Thrust Characteristics of a Downstream Offshore Floating Wind Turbine under Yawed Inflow Conditions - Yangwei Wang; Jiahuan Lin; Huawei Duan; Jun Zhang (Journal of Marine Science and Engineering, 2021)
In the natural marine environment, offshore floating wind turbines (OFWTs) inevitably experience yawed inflow conditions, which will make their aerodynamics more complicated than those experiencing uniform inflow conditions and difficult to understand. In the present study, the thrust characteristics of a wake-influenced OFWT under dynamic, static, and coupled yawed inflow conditions are investigated thoroughly. Analytical characterizations of yawed inflow and upstream wake are integrated into the blade element momentum (BEM) method to achieve the investigation. Based on this method, simulations by the FAST code have been conducted, and the results are analyzed. It is shown that the three inflow conditions have considerable influences on the thrust coefficient of the wind rotor or the normal force at the blade section, especially in the wake case where the downstream OFWT is located at a specific offset from the central line of a single upstream wake. In order to validate the analyses of simulation results, experimental tests by a set of dedicated apparatus are conducted. The comparison results are good, proving the reliability of simulation results. This work can provide some theoretical contributions to the aerodynamic design and control of OFWTs.

Rapid diagnosis of Ralstonia solanacearum infection sweet potato in China by loop-mediated isothermal amplification - Huawei Li; Hong Zhang; Zhonghua Liu; Zhijian Lin; Yongxiang Qiu; Hao Tang; Sixin Qiu (Archives of Microbiology, 2021)

Geochemical Appraisal of Chemical Weathering and Metal Contamination in Coastal Surface Sediments, Off Northwest Hainan Island, the Gulf of Tonkin - Dawei Liu; Baozhi Lin; Selvaraj Kandasamy; Huawei Wang; Qianqian Liu; Wenbin Zou; Aimei Zhu; Jianjun Zou; Jiann-Yuh Lou; Xuefa Shi (Frontiers in Marine Science, 2019)

Manipulating mRNA splicing by base editing in plants - Chenxiao Xue; Huawei Zhang; Qiupeng Lin; Rong Fan; Caixia Gao (Science China Life Sciences, 2018)

Sorting nexin (MoVps17) is required for fungal development and plant infection by regulating endosome dynamics in the rice blast fungus - Huawei Zheng; Zhongkun Guo; Yang Xi; Mingyue Yuan; Yahong Lin; Congxian Wu; Yakubu Saddeeq Abubakar; Xianying Dou; Guangpu Li; Zonghua Wang; Wenhui Zheng; Jie Zhou (Environmental Microbiology, 2017)
Summary Vps17 is a sorting nexin (SNX) and a component of the retromer, a protein complex mediating retrograde vesicle transport between endosomes and the trans‐Golgi network. However, its role in the development and pathogenicity of filamentous fungi such as the rice blast fungus ( Magnaporthe oryzae ) remains unclear. We investigate the functional relationship between the SNX and the cargo‐selective complex (CSC) of the fungal retromer by genetic analysis, live cell imaging and immunological assay. Our data show that the MoVps17 null mutation causes defects in growth, development and pathogenicity in M. oryzae . MoVps17 is localized to endosomes depending on the activity of phosphatidylinositol 3‐kinase (PI3K), a key enzyme for fungal development and infection. Both PX and BAR domains of MoVps17 are essential for its endosomal localization and function. Furthermore, our yeast two‐hybrid assays show that MoVps17 and MoVps5 can interact. Lastly, live cell imaging suggests that MoVps17 can regulate early endosome fusion and budding as well as endocytosis. Taken together, our results suggest that MoVps17 specifically functions as a retromer component with CSC and also plays a distinct role in the regulation of endosome dynamics during fungal development and plant infection.

Migration of endophytic diazotroph Azorhizobium caulinodans ORS571 inside wheat (Triticum aestivum L) and its effect on microRNAs - Li Qiu; Qiang Li; Junbiao Zhang; Yongchao Chen; Xiaojun Lin; Chao Sun; Weiling Wang; Huawei Liu; Baohong Zhang (Functional & Integrative Genomics, 2017)

Developing Single Nucleotide Polymorphism (SNP) Markers for the Identification of Coffee Germplasm - Lin Zhou; Fernando E. Vega; Huawei Tan; Aixa E. Ramírez Lluch; Lyndel W. Meinhardt; Wanping Fang; Sue Mischke; Brian Irish; Dapeng Zhang (Tropical Plant Biology, 2016)

Identification of a novel compound heterozygous mutation in PTPRQ in a DFNB84 family with prelingual sensorineural hearing impairment - Qing Sang; Honglin Mei; Ahan Kuermanhan; Ruizhi Feng; Luo Guo; Ronggui Qu; Yao Xu; Huawei Li; Li Jin; Lin He; Lei Wang (Molecular Genetics and Genomics, 2015)

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon - Huawei Duan; Zhini He; Junxiang Ma; Bo Zhang; Zhiguo Sheng; Ping Bin; Juan Cheng; Yong Niu; Haiyan Dong; Han Lin; Yufei Dai; Benzhan Zhu; et al. (Archives of Toxicology, 2013)